Post-valuation quality check of multiple-choice questions - Jaiswal, Kavita M.; Dudhgaonkar, Sujata; Gharade, Piyush; Sharma, Nikita (International Journal of Basic & Clinical Pharmacology, 2022)
Background: Multiple choice questions find important place in assessment in medical curriculum. Each MCQ is called item. Item analysis is quality check of MCQs after valuation of response sheets. This serves to recognize flaws in MCQs so that the given questions can be preserved in question bank, modified or deleted. Methods: 140 medical students of second MBBS were assessed pharmacology through 20 single best response type MCQ. Post exam validation of MCQs was done by item analysis. Each item was analyzed for level of difficulty, ability of the question to discriminate between poor and good performing students and distracter effectiveness. Results: Score ‘1’ was given for correct and ‘0’ for incorrect or no response. The mean score of the test was found to be 10.58±2.48, with a range 5-18. The whole test had an acceptable difficulty level with 43.25±17.81 mean difficulty index. The discrimination index of the whole test was found to be 0.123±0.184 mean PBI correlation coefficient, which is not satisfactory. Out of 60 distractors, 51 were found to be functional, hence distractor efficiency of the given test was 85%±19.96% which is acceptable. Conclusions: 60% questions were found to be ideal and 25% were acceptable with revision of stem or options. One question was easy with poor discrimination which needs major modification in construct or subject to be placed in question bank while another one question was difficult but had negative biserial index which needs to be deleted from the question bank.